2003
DOI: 10.1152/ajpregu.00355.2002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise elicits phase shifts and acute alterations of melatonin that vary with circadian phase

Abstract: Buxton, Orfeu M., Calvin W. Lee, Mireille L'HermiteBalé riaux, Fred W. Turek, and Eve Van Cauter. Exercise elicits phase shifts and acute alterations of melatonin that vary with circadian phase. Am J Physiol Regul Integr Comp Physiol 284: R714-R724, 2003; 10.1152/ajpregu. 00355.2002To examine the immediate phase-shifting effects of high-intensity exercise of a practical duration (1 h) on human circadian phase, five groups of healthy men 20-30 yr of age participated in studies involving no exercise or exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
202
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(222 citation statements)
references
References 30 publications
11
202
1
8
Order By: Relevance
“…The phase response curve of exercise on the human circadian pacemaker was reported by Buxton et al 23) . Their data indicated that evening exercise induced a phase advance and night exercise induced phase delay; morning and afternoon exercise had no effect on the circadian phase.…”
Section: Effect Of Exercise On the Circadian Pacemakermentioning
confidence: 64%
“…The phase response curve of exercise on the human circadian pacemaker was reported by Buxton et al 23) . Their data indicated that evening exercise induced a phase advance and night exercise induced phase delay; morning and afternoon exercise had no effect on the circadian phase.…”
Section: Effect Of Exercise On the Circadian Pacemakermentioning
confidence: 64%
“…Klerman et al (1998) (21) found a phase advance when the PE was performed 6 hours after wake up time. Buxton et al (2003) (18) also verified an advance. However, the PE was performed at the beginning of the night, about 6:30 p.m.…”
Section: Physical Exercise As a Non-photic Synchronizermentioning
confidence: 66%
“…There is massive evidence that PE may act as a non-photic synchronizer, being able to dislocate the circadian rhythms phase (17)(18)(19)(20)(21)(22)(23)(24) . This phenomenon may be observed when PE is applied in constant situations, in which the influence of other synchronizers both photic and non-photic are tried to be blocked.…”
Section: Physical Exercise As a Non-photic Synchronizermentioning
confidence: 99%
See 1 more Smart Citation
“…Basic studies [62][63][64][65] to elucidate the acute phaseshifting effects of exercise measured parameters revealing the human body clock such as plasma melatonin and core body temperature for two to three successive days under a controlled situation to exclude the masking effects of 311 JPFSM : Human circadian rhythms and exercise behavior and environment. Other studies examined the effects of exercise when the sleep time of the subjects was delayed [66][67][68] or advanced [69][70][71][72] .…”
Section: Effects Of Exercise On Human Circadian Rhythmsmentioning
confidence: 99%